(untitled) (Scientific journal of the Fergana State University, 2023)
In this scientific article, gluttony discourse is one of the ways to reveal the unique characteristics of language in the process of communication related to food, if the process of food consumption is a reflection of the ethnic and religious views of nations, then "food" is the gastronomic communication of this nation. a series of characteristic semiotic features, taking the main place as a dominant concept embodying spiritual unity, understanding the gluttonous discourse in the clash of two languages ​​and cultures, requires awareness of a number of linguistic and non-linguistic factors. Just as the perceptions of people of two different cultures about the world are expressed differently in language, the synthesis of food and related processes in the human mind is different.